Calcifediol boosts efficacy of ChAdOx1 nCoV-19 vaccine by upregulating genes promoting memory T cell responses - Saroha, Himanshu Singh; Bhat, Swati; Das, Liza; Dutta, Pinaki; Holick, Michael F.; Sachdeva, Naresh; Marwaha, Raman Kumar (npj vaccines, 2024)
The ChAdOx1 nCoV-19 (COVISHIELD) vaccine has emerged as a pivotal tool in the global fight against the COVID-19 pandemic. In our previous study eligible subjects were supplemented with calcifediol, a direct precursor to the biologically active form of vitamin D, calcitriol with an objective to enhance the immunogenicity of the COVISHIELD vaccine. Herein we investigated the effects of calcifediol supplementation on gene expression profiles in individuals who received the COVISHIELD vaccine. Peripheral blood mononuclear cells were isolated from vaccinated individuals with and without calcifediol supplementation at baseline, 3rd and 6th month, and the gene expression profiles were analyzed using high-throughput sequencing. The results revealed distinct patterns of gene expression associated with calcifediol supplementation, suggesting potential molecular mechanisms underlying the beneficial effects of calcifediol in improving the efficacy of COVISHIELD vaccine via augmentation of T cell activation, proliferation and T cell memory responses. Additionally, there was upregulation of NOD like receptor, JAK/STAT and TGF beta signaling pathways. Calcifediol supplementation in vaccinated individuals also downregulated the pathways related to the Coronavirus disease. Taken together, our findings provide valuable insights into the interplay between vitamin D receptor (VDR) signaling and vaccine-induced immune responses and offer another approach in improving vaccination induced antiviral responses.